1998
DOI: 10.1121/1.421120
|View full text |Cite
|
Sign up to set email alerts
|

Free and forced in-plane vibration of rectangular plates

Abstract: A mathematical model is developed for the prediction of the forced response of finite plates to in-plane point force excitations. The model illustrates the nature of the coupling between in-plane longitudinal and in-plane shear waves and the resonant characteristics of the in-plane vibrational behavior of finite flat plates. The predicted resonance frequencies and mode shapes are compared against the finite element results and good agreement is found. The mode shapes of the in-plane vibration are depicted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 4 publications
0
25
0
1
Order By: Relevance
“…These results are compared to those computed by Kantorovich method [29], forced response analysis based on two different formulations [27,28], the Fourier series based analytical method [32] and the finite element solutions by using NASTRAN taken from [28]. It is found that the results obtained by the forced response analysis in [27] and Fourier series based analytical methods [32] match better with the current SDSM compared to the other three methods. The Kantorovich method [29], being a weak formulation, always give upper bound solution of the SDSM results, as expected.…”
Section: Applications To Plane Stress Problemsmentioning
confidence: 82%
See 3 more Smart Citations
“…These results are compared to those computed by Kantorovich method [29], forced response analysis based on two different formulations [27,28], the Fourier series based analytical method [32] and the finite element solutions by using NASTRAN taken from [28]. It is found that the results obtained by the forced response analysis in [27] and Fourier series based analytical methods [32] match better with the current SDSM compared to the other three methods. The Kantorovich method [29], being a weak formulation, always give upper bound solution of the SDSM results, as expected.…”
Section: Applications To Plane Stress Problemsmentioning
confidence: 82%
“…The (k, j) notation is the same as that given in Table 3. a Kantorovich method [29] b Forced response analysis 1 [28] c Forced response analysis 2 [27] d finite element solution using NASTRAN [28] e Fourier series based analytical method [32] Figure 4: The first eight non-zero free inplane vibration mode shapes of a completely free square (a/b = 1) isotropic plate. The (k, j) notation and the meaning of colour of mesh is the same as those in Table 3.…”
Section: Applications To Plane Stress Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…At present times piezoelectric ceramic transducers in longitudinal vibration with matching layers and transducers in flexural vibration are both used in a gas environment [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99]. Using transducers in a flexural vibration gives the best possibility to match acoustic impedances of air and the transducer, because flexural transducers have a sufficiently low acoustic impedance.…”
Section: Acoustic Antennas For Devices Using a Direct Ultrasonic Poromentioning
confidence: 99%